Perspectives on perceived stigma and self-stigma in adult male patients with depression - Latalova K; Kamaradova D; Prasko J (Neuropsychiatric Disease and Treatment, 2014)
Klara Latalova, Dana Kamaradova, Jan Prasko Department of Psychiatry, Faculty of Medicine and Dentistry, University Palacky Olomouc, Olomouc, Czech Republic Abstract: There are two principal types of stigma in mental illness, ie, “public stigma” and “self-stigma”. Public stigma is the perception held by others that the mentally ill individual is socially undesirable. Stigmatized persons may internalize perceived prejudices and develop negative feelings about themselves. The result of this process is “self-stigma”. Stigma has emerged as an important barrier to the treatment of depression and other mental illnesses. Gender and race are related to stigma. Among depressed patients, males and African-Americans have higher levels of self-stigma than females and Caucasians. Perceived stigma and self-stigma affect willingness to seek help in both genders and races. African-Americans demonstrate a less positive attitude towards mental health treatments than Caucasians. Religious beliefs play a role in their coping with mental illness. Certain prejudicial beliefs about mental illness are shared globally. Structural modeling indicates that conformity to dominant masculine gender norms (“boys don’t cry”) leads to self-stigmatization in depressed men who feel that they should be able to cope with their illness without professional help. These findings suggest that targeting men’s feelings about their depression and other mental health problems could be a more successful approach to change help-seeking attitudes than trying to change those attitudes directly. Further, the inhibitory effect of traditional masculine gender norms on help-seeking can be overcome if depressed men feel that a genuine connection leading to mutual understanding has been established with a health care professional. Keywords: stigma, self-stigma, depression, male gender